Plasmid metagenome reveals high levels of antibiotic resistance genes and mobile genetic elements in activated sludge. - Tong Zhang; Xu-Xiang Zhang; Lin Ye (PLoS ONE, 2011)
The overuse or misuse of antibiotics has accelerated antibiotic resistance, creating a major challenge for the public health in the world. Sewage treatment plants (STPs) are considered as important reservoirs for antibiotic resistance genes (ARGs) and activated sludge characterized with high microbial density and diversity facilitates ARG horizontal gene transfer (HGT) via mobile genetic elements (MGEs). However, little is known regarding the pool of ARGs and MGEs in sludge microbiome. In this study, the transposon aided capture (TRACA) system was employed to isolate novel plasmids from activated sludge of one STP in Hong Kong, China. We also used Illumina Hiseq 2000 high-throughput sequencing and metagenomics analysis to investigate the plasmid metagenome. Two novel plasmids were acquired from the sludge microbiome by using TRACA system and one novel plasmid was identified through metagenomics analysis. Our results revealed high levels of various ARGs as well as MGEs for HGT, including integrons, transposons and plasmids. The application of the TRACA system to isolate novel plasmids from the environmental metagenome, coupled with subsequent high-throughput sequencing and metagenomic analysis, highlighted the prevalence of ARGs and MGEs in microbial community of STPs.